2020
DOI: 10.1016/j.ygcen.2019.113247
|View full text |Cite
|
Sign up to set email alerts
|

Under the weather: Corticosterone levels in wild nestlings are associated with ambient temperature and wind

Abstract: Animals time reprocluctive events to overlap with periocls of favorable environmental conditions. However, weathet conditions can be unpredictable. Young animals may be particularly susceptible to extreme weather during sensitive developmental periods. Here, we investigated the effects of adverse weather conditions on corticosterone levels {a hormone linked to the avian stress resp0nse) and body condition of wild nestling zebra finches (Taeniopygia guttata). We sowght to tease apart the direct versus indirect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…89 Study site and system 90 Fieldwork was conducted at the Kuruman River Reserve (33 km 2 , KRR; 26°58'S, 91 21°49'E) in the southern Kalahari. Mean summer daily maximum temperatures at the study site, 92 from 1995-2015, averaged 34.7 ± 9.7°C and mean annual precipitation averaged 186.2 ± 93 87.5mm [49].…”
Section: Methodsmentioning
confidence: 99%
“…89 Study site and system 90 Fieldwork was conducted at the Kuruman River Reserve (33 km 2 , KRR; 26°58'S, 91 21°49'E) in the southern Kalahari. Mean summer daily maximum temperatures at the study site, 92 from 1995-2015, averaged 34.7 ± 9.7°C and mean annual precipitation averaged 186.2 ± 93 87.5mm [49].…”
Section: Methodsmentioning
confidence: 99%
“…For example, a recent study has found that in the hottest parts of Australia, the most significant climatic constraint on avian reproduction is ambient temperature during the late spring and summer ). Furthermore, nestlings reared in hot conditions were found to attain a smaller adult body size than those raised in more moderate ambient temperatures, both observationally and experimentally (Andrew et al 2017), and have a lower stress response at high temperatures (Crino et al 2020). Adults, are likely to be physiologically challenged by temperatures that are close to, or exceed, around 35°C (Smit et al 2013, Funghi et al 2019, and so we might expect that egg size is negatively related to the ambient temperature during the laying period.…”
Section: Introductionmentioning
confidence: 96%
“…Adverse weather conditions impair nestling development Imlay et al 2018) by causing a trade-off between devoting energy to thermoregulation or to growth (Dawson et al 2005). High temperatures constrain nestling growth (Cunningham et al 2013;Andreasson et al 2018), result in smaller nestlings overall (Salaberria et al 2014;Wada et al 2015;Rodriguez and Barba 2016), alter corticosterone levels (Newberry and Swanson 2018;Crino et al 2020) and reduce survival probabilities (Greño et al 2008;Zuckerberg et al 2018;Bourne, Cunningham, et al 2020a). Higher rainfall often has a positive effect on nestling development (Wiley and Ridley 2016) and survival (Skagen and Yackel Adams 2012;Mares et al 2017), at least in arid and semi-arid ecosystems (Cumming and Bernard 1997;Hidalgo Aranzamendi et al 2019), although see Morganti et al (2017) and Cox et al (2019) for effects of rainy weather in temperate environments.…”
Section: Introductionmentioning
confidence: 99%